Leucophyllum frutescens mediated synthesis of silver and gold nanoparticles for catalytic dye degradation - Gami, Bansuri; Bloch, Khalida; Mohammed, Shahansha M.; Karmakar, Srikanta; Shukla, Satyajit; Asok, Adersh; Thongmee, Sirikanjana; Ghosh, Sougata (Frontiers in Chemistry, 2022)
The application of nanotechnology is gaining worldwide attention due to attractive physico-chemical and opto-electronic properties of nanoparticles that can be also employed for catalytic dye degradation. This study reports a phytogenic approach for fabrication of silver (AgNPs) and gold nanoparticles (AuNPs) using Leucophyllum frutescens (Berl.) I. M. Johnst (Scrophulariaceae) leaf extract (LFLE). Development of intense dark brown and purple color indicated the synthesis of AgNPs and AuNPs, respectively. Further characterization using UV-visible spectroscopy revealed sharp peak at 460 nm and 540 nm for AgNPs and AuNPs, respectively that were associated to their surface plasmon resonance. High resolution transmission electron microscope (HRTEM) revealed the spherical shape of the AgNPs, whereas anisotropic AuNPs were spherical, triangular and blunt ended hexagons. The majority of the spherical AgNPs and AuNPs were ∼50 ± 15 nm and ∼22 ± 20 nm, respectively. Various reaction parameters such as, metal salt concentration, temperature and concentration of the leaf extract were optimized. Maximum synthesis of AgNPs was obtained when 5 mM for AgNO3 reacted with 10% LFLE for 48 h at 50°C. Likewise, AuNPs synthesis was highest when 2 mM HAuCl4 reacted with 10% LFLE for 5 h at 30°C. Energy dispersive spectroscopy (EDS) showed phase purity of both the nanoparticles and confirmed elemental silver and gold in AgNPs and AuNPs, respectively. The average hydrodynamic particles size of AgNPs was 34.8 nm while AuNPs was 140.8 nm as revealed using dynamic light scattering (DLS) that might be due to agglomeration of smaller nanoparticles into larger clusters. ZETA potential of AgNPs and AuNPs were 0.67 mV and 5.70 mV, respectively. X-ray diffraction (XRD) analysis confirmed the crystallinity of the nanoparticles. Fourier transform infrared spectroscopy (FTIR) confirmed that various functional groups from the phytochemicals present in LFLE played a significant role in reduction and stabilization during the biogenic synthesis of the nanoparticles. The bioreduced AgNPs and AuNPs catalytically degraded Rhodamine B dye (RhB) in presence of UV-light with degradation rate constants of 0.0231 s−1 and 0.00831 s−1, respectively. RhB degradation followed a first order rate kinetics with 23.1 % and 31.7% degradation by AgNPs and AuNPs, respectively.